1984
DOI: 10.1073/pnas.81.8.2494
|View full text |Cite
|
Sign up to set email alerts
|

Ly-1 B cells: functionally distinct lymphocytes that secrete IgM autoantibodies.

Abstract: Studies presented here introduce another perspective on the mechanisms responsible for IgM autoantibody production. A unique subpopulation of B lymphocytes (Ly-1 B) that concomitantly expresses IgM, IgD, Ia, and Ly-1 membrane glycoproteins is present at higher frequencies in NZB and NZB-related mice. The Ly-1 B subpopulation in these autoimmune dinials is responsible for the "spontaneous" IgM secretion demonstrated with cultured JNZB spleen cells and contains the cells that secrete typical NZB IgM autoantibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
315
1
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(326 citation statements)
references
References 15 publications
8
315
1
2
Order By: Relevance
“…The enrichment of autoreactive specificities in the B1a B cell compartment [8][9][10][11][12], their low activation threshold and the increased numbers of B1 B cells in various murine lupus models [4,6] have led to the speculation of involvement of these cells in the pathogenesis of autoimmunity. This assumption is supported by studies showing amelioration of murine lupus when B1 B cells were either genetically or physically depleted [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enrichment of autoreactive specificities in the B1a B cell compartment [8][9][10][11][12], their low activation threshold and the increased numbers of B1 B cells in various murine lupus models [4,6] have led to the speculation of involvement of these cells in the pathogenesis of autoimmunity. This assumption is supported by studies showing amelioration of murine lupus when B1 B cells were either genetically or physically depleted [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the PC they can be detected in the spleens, blood and inflamed target organs [7]. Human and murine B1a B cells are enriched for autoreactive specificities targeting DNA, thymocytes, immunoglobulins and phosphatidylserine [8][9][10][11][12]. B1 cells have additionally been shown to be the source of anti-erythrocyte antibodies in a transgenic model of autoimmune hemolytic anemia [13].…”
Section: Introductionmentioning
confidence: 99%
“…The proliferating cell in CLL is a CD5+ B cell, which may produce monoclonal IgM-RF sharing a cross-reactive idiotype with RF produced by patients with SS (13,14). Genetically susceptible autoimmune strains of mice also manifest increased numbers of CD5+ B -PHA cells (termed Ly-l), which produce autoantibodies such as anti-erythrocyte and anti-DNA (15). Aged autoimmune mice develop clonal proliferation of Ly-l+ B cells that may be analogous to the B cell lymphomas that arise in humans with primary SS (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice demonstrated that a cell analogous to the human CD5-t B cell and expressing cell surface Ly-1 is increased in number in autoimmune mice and becomes clonal in aged mice (15)(16)(17). Recent studies in normal mice suggest that these unusual B cells may have regulatory properties and helper function (18).…”
Section: B Cells Expressing Cd5 Are Increased In Sjogren's Syndrome Mmentioning
confidence: 99%
“…This is marked by a diminished ability for intracellular Ca 2ϩ mobilization, aberrant proliferation, and increased apoptosis after BCR cross-linking (6,7,9,10). While B-1 cells only comprise a small percentage of all B cells, they are the primary source of the serum Ab in unimmunized mice, known as natural Ab (3,11,12). The majority of natural Ab is low affinity and polyreactive, with the ability to recognize autoantigens as well as those from bacterial and parasitic sources.…”
mentioning
confidence: 99%